Understanding spelling - Seaton, Anne (Learners publishing, 2002)
A practical guide to spelling, one aspect of English that baffles learners and the native speakers themselves. the book is systematic in approach, gives clear explanations of the rules and exceptions and covers British and American spelling conventions.